EFFECT OF DIFFERENT MEDIA COMPOSITIONS OF 2,4-D, DICAMBA, AND PICLORAM ON CALLUS INDUCTION IN WHEAT (TRITICUM AESTIVUM L.) - ASHRAF, A; AMHED, N; SHAHID, M; ZAHRA, T; ALI, Z; HASSAN, A; AWAN, A; BATOOL, S; RAZA, MA; IRFAN, U; MAQSOOD, Z; KHALID, MN; et al. (Biological and Clinical Sciences Research Journal, 2022)
Wheat is a major cereal crop grown worldwide. Genus Triticum contains many species, among which T. aestivumis has commonly grown also known as bread wheat. Its genome is hexaploid, containing 42 chromosomes (2n=6x=42). To improve the response of wheat cultivars against biotic and abiotic stresses, it is genetically engineered with different biotechnological tools. Tissue culture technology has been proved vital for improving crop species in different quality and yield-related traits. Being a monocotyledons plant, wheat shows recalcitration toward tissue culture. The response of wheat to regeneration can be improved by using different growth-promoting hormones. The proposed study’s objective was to increase callus induction’s efficiencyproposed study was to increase the efficiency of callus inductionproposed study’s objective was to increase callus induction’s efficiency using different treatment of growth regulators. MS media with varying concentrations of 4, 8, and 12 mg/L of dicamba, 2, 4-D, and picloram was used to check their effect on callus induction in common wheat cultivars Anaj-2017 and Akbar-2019. Media complemented with picloram at 8 mg/L was the supreme efficiency. About 511 mg and 420 mg of callus formation were observed at 8 mg/L for picloram succeeded by dicamba which was 340 mg and 350 mg at 12 mg/L, and then by 2, 4-D, which was 112 mg and 236 mg at 8 mg/L from matured embryos of Anaj-2017 and Akbar-2019 respectively.